Formulation and Evaluation of Transdermal Patch Preparations from Ethanol Extract of Green Tea Leaves (Camellia sinensis (L.) Kuntze) - Maesaroh, Imas; Anjani, Sri (Universitas Ahmad Dahlan, 2025)
Green tea (Camelia sinensis (L.) Kuntze) contains secondary metabolites such as polyphenols, flavonoids, tannins, and catechins Epigallocatechin gallate (EGCG). An ethanol extract of green tea is formulated into a transdermal patch to bypass the first-pass effect and maintain the drug's bioavailability in the plasma. This study aims to determine the optimal concentration combination of HPMC (Hydroxypropyl Methylcellulose) and PVP (Polyvinylpyrrolidone) that yields the best physical stability of the transdermal patches. Green tea was extracted using the maceration method with 70% ethanol. Transdermal patches are made by first optimizing the base using a combination of HPMC and PVP polymer bases in F1 (1:3), F2 (2:2), and F3 (3:3). The patch preparations obtained were tested, including organoleptic evaluations, pH levels, weight consistency, thickness, and fold resistance. The results obtained show that the most optimal formula to be used as a transdermal patch preparation is formula 3 (F3), with a ratio of HPMC and PVP (3:1) and an average weight of 0.08 g and an average thickness of the patch is 0.16 m, and has met the patch fold resistance test, namely more than or equal 200 folds and has a stable pH of 6. This study concludes that green tea ethanol extract can be formulated into a transdermal patch preparation with a combination of HPMC and PVP (3:1), which has the best physical stability. Keywords: Camellia sinensis (L.) Kuntze.), HPMC-PVP, transdermal patch